PERSPEKTIF HUKUM ISLAM TERHADAP AKAD BAI’ ISTIGHLAL SEBAGAI SOLUSI PEREKONOMIAN KONTEMPORER - Ubaidillah, Ubaidillah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2023)
Abstract Bai' Istighlal is a merger between the Bai' Wafa' and Ijaroh contracts. That is, the goods are sold by Bai' Wafa', then the seller rents the goods back. This means that the buyer takes advantage of the item by renting it out to the seller himself. Bai' Istighlal is like becoming a hilah to get benefits in doing business, especially in businesses that operate according to sharia. The results of research regarding the implementation of the Bai'Istighlal contract are that the practice that occurs is in accordance with the provisions of the view of the scholars who allow in Bai' Istighlal. Where in practice the buyer leases wafa goods to the seller, after the sale and purchase agreement is completed. And the existence of a wafa' agreement in the sale and purchase agreement occurs after the sale and purchase agreement is completed and before the implementation of the ijaroh contract. So that it allows buyers to rent their goods to anyone, including members (the seller himself). Keywords: Islamic Legal Perspective, Bai' Istighlal, contemporary